Seeking Transitiona Justice In Indonesia: Lessons From The Cases of Aceh, Papua And East Timor - Manan, Munafrizal (Constitutional Review, 2015)
This article analyses the Indonesian efforts to resolve past human rights abuses under the mechanism of transitional justice following the downfall of President Soeharto on May 21, 1998. The focus of analysis is the implementation of transitional justice in the cases of Aceh, Papua, and East Timor during the transitional period. This article shows that the efforts to enforce transitional justice in these cases have been faced with obstacles. Although there have been notable efforts in terms of both judicial and non-judicial to enforce transitional justice, the final results are not satisfactory. Transitional justice mechanism to resolve past human rights abuses was implemented only with half-baked and supported with half-hearted. As a result, it has failed to bring justice for the victims. There are lessons can and should be learned from these transitional justice cases for resolving other past human rights abuse cases in Indonesia today. The current Indonesian government should pay attention to the lessons in order to resolve past human rights violations in accordance with its promise during presidential election campaign in 2014. Otherwise, it is likely to repeat the same mistake and failure of justice dealing with past human rights violations.